New Sandwich‐Type Enzyme‐Linked Immunosorbent Assay for Human MxA Protein in a Whole Blood Using Monoclonal Antibodies Against GTP‐Binding Domain for Recognition of Viral Infection - Kawamura, Mizuho (J Clin Lab Anal, 2012)
OBJECTIVES: To develop a clinically significant and practical enzyme‐linked immunosorbent assay (ELISA) for the detection of MxA protein in human whole blood, a biological marker of viral infection. DESIGN AND METHODS: A sandwich ELISA suitable for the measurement of human MxA protein in whole blood was developed using mouse monoclonal antibodies (mAbs) raised against the GTP‐binding domain of human MxA protein. Prior to the assay, the whole blood sample was treated with special buffer to extract the MxA protein, improve its stability, and avoid interference from hemoglobin. RESULTS: This ELISA meets all the requirements for use in routine clinical assays, especially in terms of sensitivity (detection limit: 1.3 ng/ml whole blood), accuracy (recovery: 93.0–100.0%), and rapidity (<1.5 h). The present ELISA had a sensitivity of100% and a specificity of 100% for viral infection when compared to samples from healthy control and 87.1% and 90.9% when compared to samples from the bacterial infection group. CONCLUSION: We have developed a new ELISA for measuring MxA protein in human whole blood using mAbs specific for the GTP‐binding domain of MxA. This ELISA has analytical performance enough for routine clinical assay and can be used in detecting the possibility of viral infection. J. Clin. Lab. Anal. 26:174‐183, 2012. © 2012 Wiley Periodicals, Inc.